Omission of dexamethasone in paclitaxel premedication regimens: protocol of the multicentre, randomised, non-inferiority DEXASTOP trial - Birgit C P Koch; Virgil A S H Dalm; Leontine E A M M Spierings; Michiel Zietse; Luuk C Aalders; Nikki De Rouw; Wouter Dercksen; Frederick W Thielen; Leni van Doorn; Roelof W F van Leeuwen (BMJ Open)
Introduction Standard premedication for paclitaxel-based chemotherapy includes dexamethasone and an histamine 1-antagonist to prevent hypersensitivity reactions (HSRs). However, the pharmacological rationale for dexamethasone is limited, and its use is associated with adverse effects such as hyperglycaemia, insomnia and immunodeficiency, negatively impacting health-related quality of life (HRQoL). No clear link has been established between dexamethasone dose, administration route and HSR incidence. Previous studies suggest that discontinuing dexamethasone beyond the second administration does not increase HSR risk. Despite this, dexamethasone remains standard practice. This trial evaluates whether complete omission of dexamethasone as paclitaxel premedication is non-inferior to the standard regimen in preventing clinically relevant HSRs (Common Terminology Criteria for Adverse Events (CTCAE) grade≥3).Methods The DEXASTOP trial is a prospective, multicentre, randomised, non-inferiority study conducted in four hospitals in the Netherlands. 500 adult patients receiving paclitaxel-based chemotherapy for any solid tumour indication will be randomised 1:1 to receive either standard premedication with dexamethasone or an experimental regimen without dexamethasone for up to five paclitaxel administrations. The primary endpoint is the incidence of clinically relevant HSRs (CTCAE grade≥3). Secondary endpoints include the incidence and severity of all-grade HSRs, the number of paclitaxel administrations before the first HSR, dexamethasone-related adverse events, HRQoL and cost-effectiveness from a healthcare and societal perspective.Ethics and dissemination This study has been approved by the Erasmus Medical Centre Ethics Committee (reference MEC-2024-0030, protocol version 3, May 2024). Study findings will be published open access in peer-reviewed journals and presented at national and international meetings. Results will be shared with patients, healthcare professionals and the public. Positive outcomes will be implemented in clinical practice, and trial data will be submitted to the EU Clinical Trials Information System for public access.Trial registration number NCT06118710.